The utilization of Ntchisi panic and Katherine pearl millet for summer stall feeding in Lilongwe District - Addy, B.L.; Thomas, D. (1976)
Trials were conducted at Citedze research station in Malawi between 1972-75 on two forages species, namely Ntchisi panic (Panicum maximum CV.Ntchisi) and pearl millet (Pennisteum typholdes CV. Katherine). The purpose or the study was to evaluate the two forage species performances as a green feed to summer stall feeding and asses the responses of Malawi Zebu (MZ) and teir Friesian crosses (FxZ) to the varying concentrate feed levels. The trial treatments included various levels of concentrate supplement (Maize/ Madeya) feed to MZ feeder grade steers. Forage productivity trials and intake measurement showed no significance differences between the two forage crops. Intake of forage dry matter was increased when dried leucaena leaf was included as a protein supplement. During extensive rainfall no response was reported to a high level of concentrate supplement. Animal weight gain is not significantly different between cotton seed cake and leucaena supplementations. Forage and total DM intake by Malawi Zebu (MZ) steers was 25% lower than for Friesian X Malawi Zebu (F X Z), and this was attributed to weight difference; however, intake per kg of live weight and feed conversion efficiency were similar. The poor weight gain in case of the control group indicates a need, particularly with the crossbreds to increase concentrate supplementation as forage quality declines. Differences between carcasses or the breed types were caused largely by those of size factors. There was no practical differences in dressing out percentage. Maize/ madeya with groundnut tops supplementation was the cheapest feeding system recommended to attain a live weight gain of 1.4 to 1.6 per day.